Sun Yat-sen, “400 million Chinese”, and the Fear of Demographic Stagnation in Early Twentieth-century China: - Roctus, Jasper (Journal of the European Association for Chinese Studies, 2025)
Through a concise biography of the number “400 million” (si wan wan) as used by Sun Yat-sen (1866–1925), the first provisional president of the Republic of China in 1912, this paper clarifies how and why Sun used the widespread image of a stagnating “400 million Chinese” despite the lack of evidence for this alleged population number. The article elucidates how the vagueness surrounding the image of “400 million Chinese” was attractive to Sun, as it allowed him to pragmatically adjust its (ethnic) definition along with his shifting aims. Ultimately, when systematising his philosophy in 1924, Sun used “400 million Chinese” to generate a sense of urgency for the implementation of his minzu (“Nationalism”) doctrine, the first of three doctrines constituting his chief political philosophy: the Three Principles of the People. 本文通過傳記分析，探討了孫中山（1866–1925）在缺乏確切人口數據的情況下，為何及如何廣泛使用“四萬萬中國人”這一概念。研究表明，這一模糊意象對孫中山具有吸引力，因其允許他根據政治目標的變化靈活調整他的民族定義。最終，在1924年系統化其政治哲學時，孫中山使用“四萬萬中國人”這一數字，為其“民族主義”學說的推行營造緊迫感，而該學說成為其核心政治哲學“三民主義”的重要組成部分。